2015
DOI: 10.1080/23308249.2015.1024826
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Structure of Tunas Inferred from Molecular Markers: A Review

Abstract: In this study, we have reviewed the population genetic structure of eleven tuna species (albacore, bigeye, yellowfin, Pacific bluefin, Atlantic bluefin, southern bluefin, blackfin, longtail, skipjack, frigate, and little tuna) with a global perspective. Based on the studies using molecular markers, there are 50 genetically distinct populations of tuna species worldwide (12 albacore, 4 bigeye, 9 yellowfin, 4 bluefin, 2 blackfin, 2 longtail, 12 skipjack, 2 little tuna, and 3 frigate tuna). It is evident that som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 91 publications
0
16
0
Order By: Relevance
“…For example, Ely et al. () study found no genetic differentiation between nor within oceanic basins for skipjack tuna ( Katsuwonus pelamis ) while Kumar and Kocour review () reports several stocks/populations revealed by more recent studies with different mtDNA regions. Finally, the apparent panmixia between Atlantic and Indian Ocean populations of albacore ( Thunnus alalunga ) recorded with microsatellites (Montes et al., ) was recently demonstrated with SNP as hiding substructuration (Laconcha et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ely et al. () study found no genetic differentiation between nor within oceanic basins for skipjack tuna ( Katsuwonus pelamis ) while Kumar and Kocour review () reports several stocks/populations revealed by more recent studies with different mtDNA regions. Finally, the apparent panmixia between Atlantic and Indian Ocean populations of albacore ( Thunnus alalunga ) recorded with microsatellites (Montes et al., ) was recently demonstrated with SNP as hiding substructuration (Laconcha et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The misspecification of genetically different populations may lead to management that negatively affects productivity and long-term stability of tuna populations, as well as the capacity of populations to respond to the variability of oceanic conditions and fishing pressures 5 , 6 . Designing stock-specific management plans and conservation policies tailored to life history traits, genetic structure and ecological dynamics would mitigate the risk of stock decline and irreversible collapse 1 , 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…high fecundity and large population size) that make it difficult to detect fine-scale genetic differentiation among populations by analysing only a few individuals and a small number of neutral loci (i.e. microsatellites, mitochondrial DNA) representative of a limited portion of the whole genetic variability 5 , 7 , 11 , 12 . The recent introduction of genome-wide Single Nucleotide Polymorphism (SNP) genotyping has increased the accuracy and speed of population genetic analyses at relatively low costs.…”
Section: Introductionmentioning
confidence: 99%
“…When investigating the population structure of a particular species, the limitations of the given study should always be considered. Furthermore, identification of the population structure is not always straightforward and there are cases where detection of genetic heterogeneity fails, despite its presence [ 58 ].…”
Section: Discussionmentioning
confidence: 99%